Metadata for information governance - García-Morales, Elisa (Anuario ThinkEPI, 2015)
In the emerging context of data proliferation on digital media, the importance of metadata is becoming apparent. Records managers and librarians have been working many years on metadata conceptualization and standardization for digital humanities and recordkeeping purposes. The lessons learned should serve these new needs. Metadata are key elements in information governance and require global vision, conceptual clarity and accountability.
Keywords: Metadata; Big content; Information governance; Data management; Records management.